RACE AGAINST THE DEADLINE : ANALISIS FAKTOR KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN INDEKS LQ-45 - Muhammad Rayhan Habibie; Elok Heniwati; Vitriyan Espa (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to examine the effect profitability, leverage, Good Corporate Governance, and firm size and the timeliness of reporting for companies in the LQ-45 index during the 2020–2024 period. The method employed is logistic regression using secondary data from annual reports. The results indicate that profitability, leverage, and firm size do not significantly impact reporting timeliness, while Good Corporate Governance does have a significant effect. The model explains only 12.3% of the variance in reporting timeliness, suggesting that many other factors beyond those studied are at play. These findings underscore the need to balance internal oversight with reporting process efficiency.